Influence of Safety and Health Job Factor to Work Productivity Employees (Case Study to Employees Part of Production in PT. Gatra Mapan I, Malang) - Deoranto, Panji; Astuti, Retno; Mahmudi, Heru (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The research was aimed at examining the influence of the availability of occupational safety and health factors on the productivity of employees at a particular furniture industry located in Malang town. A survey-type research was conducted employing a pre-determined questionnaire involving five main variables, namely the safety factors, work-place accident coverage, health and rest facilities, health benefits and physical environment of the work-place. Each of which was represented by 3-4 related aspects. As many as 78 employees were taken by means of simple random sampling as respondents. A scale scoring technique introduced by Likert was used to rate the degree of employees’ satisfaction upon the availability of such factors. The productivity of the employees per month was measured by the ratio of the value of output (value in Rupiahs of the sold products) to the input, i.e. total salaries or wages in Rupiahs paid to the employees of the corresponding month. The measurement was conducted in two consecutive months, from March to April 2006. The results showed that the occupational safety and health factors in the studied furniture industry were quite good. The productivity was certainly influenced by such variables. And their relation maybe expressed as Y = 9.494 + 0.379 X1 + 0.249 X2 + 0.571 X3 + 0.239 X4 + 0.284 X5 + e, where Y is the productivity and X1 to X5 are the safety factors, work-place accident coverage, health and rest facilities, health benefits, physical environment of the work-place and e is the degree of error respectively. Keywords : Productivity, Occupational Safety and Health Factors, Employees